Advances in human aspects of aviation - Landry, Steven J. (Advances in human factors and ergonomics series, 2013)
With contrbutions from experts, this book covers the design of aircrafts for the comfort and well being of the passenger. It includes strategies and guidelines for maximizing comfort, the design of aircrafts including cockpit design, and the training and work schedules for flight attendants and pilots.